Nudity as Strategy: Examining Femen Sextremism Ideology to Weaponize Women’s Body - Dias Pabyantara Swandita Mahayasa (JUSS (Jurnal Sosial Soedirman), 2023)
In the age of the new wave feminism movement, Femen stood out to be one of the heavily discussed topics of women's movements due to its controversial protest strategy. They are one of few feminist movements that utilize, or in their terms, weaponize, the naked body to deliver a political message. It generates various backlash, upon which they are accused of perpetuating western biased standards of beauty and marginalizing non-white women's experience. Despite the controversy, they gained international recognition from the birth of the movement in 2009 until recently. We explore the matters by examining the enabling factors supporting the global movement to endure the controversy over the last decade. We conclude that two factors play a crucial role in the movement's sustainability. First, how they encapsulate and translate the sextremism ideology into firm action. Second, Femen has developed a firm, organized, yet fluid social movement by establishing strong informal ties through soldier-like training.